Defects and diffusion studied using PAC spectroscopy - Jaeger, Herbert; Zacate, Matthew O. (Diffusion and defect data. Defect and diffusion forum, 2011)
The motivation for this special-topic volume was two-fold. Among the various techniques for probing material properties at the atomic scale, PAC is a somewhat hidden gem. This is partly because PAC requires the use of radioisotopes; thus rendering it almost useless as a non-destructive characterization method. Moreover, there are relatively few PAC isotopes available; so it is not always possible to apply PAC to the most technologically pressing problems. Thus, PAC studies of materials are often more fundamental, and less applied, in nature. One of the goals of this volume was to raise the pro.